Synthesis, Characterization and Optical Properties of New Pvc- Amines Polymers - Ahmed, Ahmed A (Al-Nahrain Journal of Science, 2018)
Poly (vinyl chloride) (PVC) react with different amines in THF to form new polymers (PVC-L). The structures of these polymers have been characterized by IR and Uv-Vis. spectrophotometry. The optical properties of pure and modified PVC were studied in the region (200-400 nm). The optical data analyzed and interpreted in term of the theory of phonon assisted direct electronic transition; it is observed that the energy is affected by doping type polymers used.